A Measure of Pure Home Bias - Cooper, Ian A; Sercu, Piet; Vanpée, Rosanne (Review of Finance, 2018)
Abstract The literature on international equity holdings distinguishes between home bias (overweighting of home stocks) and foreign bias (relative underweighting for more “distant” countries). The two biases can be integrated into one distance-based model. We define pure home bias as the excess of home bias relative to this model, and find pure home bias only in emerging markets. Countries with high tax rates and low credit standing have higher pure home bias, and more development comes with lower distance aversion. Methodologically, the choice of portfolio bias measure matters. We find the best measure to be a covariance-based measure relative to the world average.